Mitigation of emissions through energy efficiency standards for room air conditioners in Malaysia - Mahlia, T.M.I.; Masjuki, Haji Hassan; Saidur, Rahman; Amalina, M.A. (Energy Policy, 2004)
Malaysian economy has grown rapidly in the last two decades. This growth has increased the ownership of household electrical appliances including room air conditioners. The number of users of air conditioners is predicted to grow dramatically in Malaysian households in the future. To reduce energy consumption in the residential sector, the Malaysia Energy Commission is considering implementing minimum energy efficiency standards for room air conditioners in early 2004. This paper attempts to predict the potential mitigation of emissions through energy efficiency standards for room air conditioners in Malaysia. The calculations were based on the growth of room air conditioners ownership data in Malaysian households. The study found that the energy efficiency standards for room air conditioners would mitigate a significant amount of emissions in this country.